2015
DOI: 10.1111/2041-210x.12314
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone: effects on feather quality and deposition into feathers

Abstract: Summary1. The concentration of the glucocorticoid hormone corticosterone (CORT) is increasingly used in ecology and conservation biology as an integrated measure of the historical record of an individual's hypothalamo-pituitaryadrenal (HPA) activity during feather growth. However, where and how CORT is incorporated in feathers is incompletely known. 2. We therefore examined whether CORT is reliably measured with an enzyme immunoassay, where CORT is incorporated in the feather and where it affects feather quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
140
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(147 citation statements)
references
References 28 publications
5
140
2
Order By: Relevance
“…Importantly, we measured immediate corticosterone levels (when the chicks were 9-days old). It is plausible that an integrative measure of corticosterone levels (for instance, in the feathers) may provide a more accurate assessment of the stress levels experienced by the chicks throughout their development [21]. In addition, other factors could have accounted for the difference in telomere length between experimental chicks and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we measured immediate corticosterone levels (when the chicks were 9-days old). It is plausible that an integrative measure of corticosterone levels (for instance, in the feathers) may provide a more accurate assessment of the stress levels experienced by the chicks throughout their development [21]. In addition, other factors could have accounted for the difference in telomere length between experimental chicks and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Romero, Strochlic & Wingfield, 2005;DesRochers et al, 2009;Almasi et al, 2012;Jenni-Eiermann et al, 2015). Corticosterone has complex, contrasting and even opposing effects when related to food intake and feather growth.…”
Section: (4) Corticosteronementioning
confidence: 99%
“…However, Murphy et al (1988) found that synthetic diets deficient in sulfur-containing amino acids produced these pale bands without generating fault bars. Experimental studies in barn owls (Tyto alba) (Roulin et al, 2008) and feral pigeons (Columba livia) (Jenni-Eiermann et al, 2015) report increases in the frequency of pale bands in corticosterone-implanted birds (see Fig. 3 in Jenni-Eiermann et al, 2015), but they did not report the formation of fault bars.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Intra-assay coefficient of variation was 6.87 %. CORTf was expressed as pg/mm of feather, as recommended in previous works (Bortolotti et al 2008(Bortolotti et al , 2009aJenni-Eiermann et al 2015) …”
Section: Feather Corticosterone Assaysmentioning
confidence: 99%